2012
DOI: 10.1007/s00436-012-3082-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diversity of cystic echinococcosis in livestock in Maasailand, Kenya

Abstract: Cystic echinococcosis (CE) is a zoonotic disease caused by several members of the Echinococcus granulosus species complex. In East Africa, several species/strains are known to occur in livestock and humans, but host preferences, relative frequencies and spatial distribution of these taxa are poorly known. Here, we contribute livestock data for Maasailand of southern Kenya. Total CE prevalence was 25.8 % in cattle (151/587), 16.5 % in sheep (71/430) and 10.8 % in goats (21/194), which is a significant increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
4
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
9
46
4
2
Order By: Relevance
“… indicated that brain CE caused by E. canadensis (G6) was due to primary infection of the brain without hepatic lesions. This is in contrast to all other reports of E. canadensis , which indicated hepatic lesions with metastasis to the brain . It remains unclear whether this difference is due to unique genetic characteristics of the parasite, the host, or both, with genetic background postulated to be important in Iranian cases of Echinococcus .…”
Section: Topicscontrasting
confidence: 76%
“… indicated that brain CE caused by E. canadensis (G6) was due to primary infection of the brain without hepatic lesions. This is in contrast to all other reports of E. canadensis , which indicated hepatic lesions with metastasis to the brain . It remains unclear whether this difference is due to unique genetic characteristics of the parasite, the host, or both, with genetic background postulated to be important in Iranian cases of Echinococcus .…”
Section: Topicscontrasting
confidence: 76%
“…A recent epidemiological study in Kenya looking at the prevalence of hydatidosis in cattle, sheep and goats shows a significant increase compared with data about three decades ago [17]. Even the introduction of livestock from other countries after the civil war could be a factor involved in echinococcosis in a country like Mozambique, with such an abundant canine population in its rural environment.…”
Section: Discussionmentioning
confidence: 96%
“…Other than this, the host range (including human pathogenicity) is unknown; it had not been found in 353 wildebeest (Connochaetes mearnsi) in the Masai Mara conservation area of Kenya, although it is widespread there in carnivores. Likewise, it was not present among 279 genotyped Echinococcus cysts recovered from livestock from the vicinity of Kenyan national parks (Addy et al, 2012). While E. felidis has not yet been found in any canid, the susceptibility of lions as definitive hosts is not a distinguishing feature for this taxon.…”
Section: Echinococcus Felidismentioning
confidence: 98%
“…Given the ubiquitous presence of cattle and dogs as suitable hosts, the rarity of this parasite is perplexing. It may be explained by the fact, that, even in traditional pastoral societies, cattle are mostly sold alive and slaughtered in distant locations, so transmission to the local dog population is inhibited (Addy et al, 2012).…”
Section: Echinococcus Ortleppimentioning
confidence: 99%